Exploring Measures for Preventing Postoperative Nausea and Vomiting Associated with Postoperative Opioid Analgesia-Usefulness of a Combined Diphenhydramine and Diprophylline Preparation (Travelmin® Injection) - MIYAHARA, Seiji; TAJI, Daigo (THE JOURNAL OF JAPAN SOCIETY FOR CLINICAL ANESTHESIA, 2013)
We compared the efficacy of prevention of postoperative nausea and vomiting (PONV) using a combined diphenhydramine + diprophylline preparation (combined DD preparation) with that obtained using droperidol. Data from 249 patients (both men and women) who received continuous intravenous fentanyl infusion for postoperative analgesia were retrospectively analyzed. In both men and women, the suppression of PONV was significantly more marked with administration of combined DD preparation than droperidol. Furthermore, treatment with the combined DD preparation reduced the symptoms of vestibular stimulation (e.g., dizziness and floating sensation) often observed after droperidol treatment. Combined DD preparation also exerted excellent prophylactic effects in non-smoking women who had undergone inhalational anesthesia (a known high-risk group for PONV). Combined DD preparations are not expensive and are less likely to induce adverse reactions, so these preparations may be promising as alternatives for preventing PONV associated with administration of opioid analgesia.